MOTIVASI DAN PRAKTIK MEMBERI - Jefri Andri Saputra (STT Amanat Agung, 2021)
Abstract: The Church is part of the participants, together with humanitarian agencies to deal with poverty and natural disasters. The problem is that the church has not yet established a long-term deaconal service, in response to the increasing intensity of poverty and natural disasters. This condition makes the church need to have a biblical concept of giving. The text the author is referring to is 2 Corinthians 8-9. This text is a discussion of the gifts collected for the Jerusalem church. This topic is studied with hermeneutical approach through the steps of analyzing the story behind the text, the flow of the text's delivery, and the theological significance. At the end of this paper, the author finds that the role of God in the act of giving becomes the basis for building a critique of the church's social service orientation. Then the combination of koinonia-diakonia which is manifested in the formation of a diakonia institution, becomes a practical solution for effective service. Keywords: give, God's gift, 2 Corinthians, church, social service. Abstrak: Gereja adalah bagian dari partisipan, bersama dengan lembaga-lembaga kemanusiaan untuk menangani kemiskinan dan bencana alam. Masalahnya adalah gereja belum memiiki pelayanan diakonia jangka panjang, dalam merespons peningkatan intensitas kemiskinan dan bencana alam. Kondisi ini membuat gereja perlu memiliki konsep memberi yang alkitabiah. Teks yang menjadi acuan penulis adalah 2 Korintus 8-9. Teks ini adalah pembahasan mengenai pemberian yang dikumpulkan untuk jemaat Yerusalem. Topik ini dikaji dengan pendekatan hermeneutika melalui langkah-langkah analisis cerita di balik teks, alur penyampaian teks, dan makna teologis. Di akhir tulisan ini, penulis menemukan bahwa peran Allah dalam tindakan memberi, menjadi landasan untuk membangun kritik terhadap orientasi pelayanan sosial gereja. Kemudian perpaduan koinonia-diakonia yang terwujud dalam pembentukan lembaga diakonia, menjadi solusi praktis untuk pelayanan yang efektif. Kata-kata kunci: memberi, pemberian Allah, 2 Korintus, gereja, pelayanan sosial.